Answer:
The answer in the procedure
Step-by-step explanation:
we have
2x-3y=-1 ----> equation A
3x+3y=26 --> equation B
Solve the system by elimination
Adds equation A and equation B
2x-3y=-1
3x+3y=26
----------------
2x+3x=-1+26
5x=25
x=25/5
x=5
Find the value of y
substitute the value of x in equation A or equation B and solve for y
2(5)-3y=-1
10-3y=-1
3y=10+1
y=11/3
Answer:
y = -
x + ![\frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D)
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Rearrange 4y = 5x + 3 into this form by dividing the 3 terms by 4
y =
x +
← in slope- intercept form
with slope m = ![\frac{5}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D)
Given a line with slope m then the slope of a line perpendicular to it is
= -
= -
= -
, thus
y = -
x + c ← is the partial equation
To find c substitute (3, - 2) into the partial equation
- 2 = -
+ c ⇒ c = - 2 +
= ![\frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D)
y = -
x +
← equation of perpendicular line
Answer:
there should be a pic or a diagram
Step-by-step explanation:
Answer:
2(8y+9m)
Step-by-step explanation: